A collective portrait of the ex–White Guards repressed in Omsk in the case of the «Artamonov`s organization» in 1937 - D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
The article, based on an analysis of materials from the case of «Artamonov’s organization», reconstructs a generalized social portrait of residents of the Omsk region who were subjected to massive political repression during the years of the Great Terror for belonging to the command staff of the White Army during the Civil War. The theoretical basis of the study is a combination of anthropological approach, prosopographical, comparative-historical, historical-genetic and statistical methods. The purpose of the work is to analyze, in the context of the historical conditions of the Omsk region, the typical social characteristics of representatives of the former officers who became victims of mass political repression during the years of the Great Terror. In conclusion, the information potential of historical sources is assessed and further prospects for developing the topic of political mass repressions against former White Guards are outlined.